Perbaikan Kualitas Air Menggunakan Gel Lidah Buaya (Aloe vera) - Muhammad Fajar Pranata; Syarifudin A.; Munawar Raharja (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
Abstract: Water Quality Improvement Using Aloe Vera Gel. Some people on the Trikora road, Sidomulyo Permai Ujung Complex, Banjarbaru City use swamp water with turbidity levels that do not meet the requirements, namely 42 NTU. Water sources that do not meet the requirements must be processed. Aloe vera as a natural coagulant contains mucilage which contains polygalluronic acid as a coagulant with the mechanism of adsorption and incorporation. This study aims to determine the effectiveness of dose and time variation of aloe vera gel contact as a natural coagulant in reducing turbidity of swamp water. This type of research is experimental, namely to determine the optimum dose and contact time of aloe gel as a natural coagulant. The design of this study uses Postest Only Design. Data analysis usingstatistical test Two Way Analysis of Variance with α = 0.05. Turbidity level analysis results decreased after treatment of variations in dose and contact time, the optimum dose of 1.2 grams in the contact time of 20 minutes was able to reduce turbidity of 41,63% with turbidity value of 10.73 NTU, pH 4.6 and temperature of 28.5oC. It can be suggested for further research there should be an addition of natural additives that are alkaline to increase the pH of the water.